2016
DOI: 10.7448/ias.19.1.20992
|View full text |Cite
|
Sign up to set email alerts
|

Transactional sex and risk for HIV infection in sub‐Saharan Africa: a systematic review and meta‐analysis

Abstract: IntroductionYoung women aged 15 to 24 years in sub-Saharan Africa continue to be disproportionately affected by HIV. A growing number of studies have suggested that the practice of transactional sex may in part explain women's heightened risk, but evidence on the association between transactional sex and HIV has not yet been synthesized. We set out to systematically review studies that assess the relationship between transactional sex and HIV among men and women in sub-Saharan Africa and to summarize the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
146
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 68 publications
7
146
3
Order By: Relevance
“…Age disparate relationships increase AGYW's susceptibility to HIV acquisition, because older men are more likely to be HIV positive [8,20,21], whilst these partnerships are also characterised by inconsistent condom use [22][23][24] and concurrent sexual partnering [25]. Relationships are also more likely to be transactional in nature [26], which has been demonstrated to also increase HIV acquisition [27]. In addition, AGYW are vulnerable to intimate partner violence (IPV) and dominant male partner behaviours, both of which increase their susceptibility to acquiring HIV [28].…”
Section: Introductionmentioning
confidence: 99%
“…Age disparate relationships increase AGYW's susceptibility to HIV acquisition, because older men are more likely to be HIV positive [8,20,21], whilst these partnerships are also characterised by inconsistent condom use [22][23][24] and concurrent sexual partnering [25]. Relationships are also more likely to be transactional in nature [26], which has been demonstrated to also increase HIV acquisition [27]. In addition, AGYW are vulnerable to intimate partner violence (IPV) and dominant male partner behaviours, both of which increase their susceptibility to acquiring HIV [28].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, exposure to transactional sex practice and engaging in commercial sex work in this study were the reported reproductive health effects of SH. Studies also revealed that there is an association between transactional sex and HIV/STIs [54][55][56][57][58][59]. Participants in this study also mentioned STIs as the effects of SH, and it could be due to the risky nature of this practice.…”
Section: Discussionmentioning
confidence: 57%
“…HO recommended use of tenofovir-based PrEP in individuals at substantial risk of HIV, e.g., female-sex workers (FSW), men-who-have-sex-with-men (MSM) and vulnerable populations such as adolescent girls and young women (AGYW), particularly those engaged in transactional sex (7)(8)(9), as part of a combination prevention strategy (10). The South African National Department of Health subsequently rolled-out oral PrEP to select FSW sites in 2016 and approved of PrEP and universal test and treat (UTT) for HIV prevention in MSM, serodiscordant couples and AGYW in 2017 (11).…”
Section: Introductionmentioning
confidence: 99%